A new species from Mimosa subseries Polycarpae (Leguminosae, Caesalpinioideae) in the Brazilian Pantanal - Nogueira, Luan H.p.; Morales, Matías; Sartori, Ângela L.b. (Phytotaxa, 2025)
Mimosa humidicola (Leguminosae, Caesalpinioideae) is described and illustrated for the first time. It occurs exclusively in Pantanal, in wetlands and temporary flooded ponds in southern Mato Grosso and the northwest of Mato Grosso do Sul, both in the Brazilian Midwest. Morphological description and taxonomic, ecology and geographical comments are provided. It species can be distinguished by the pubescence of leaflets, the corolla-lobes carmine contrasting with its whitish filaments and the widely-oblong pods dense pubescent. We also present a synopsis for Mimosa subser. Polycarpae with an analysis of the geographical distribution, habit, and an identification key for its species in South America. Additionally, we cited a new occurrence of Mimosa balansae in the Brazilian Chaco.